Penapisan Profil Gula Darah Puasa sebagai Indikator Kesehatan pada Populasi Usia Dewasa di Sekolah Kristen Kalam Kudus 2 Jakarta - Sjaiful Bachri; Alexander Halim Santoso; Edwin Destra; Daniel Goh; Gracienne Gracienne (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Consumption of sweetened beverages contributes to increased blood glucose levels that lead to the risk of pre-diabetes and type II diabetes mellitus. Fasting blood sugar examination is an early screening tool to detect hidden metabolic disorders and educate the public about the importance of controlling sugar consumption. The examination was conducted through capillary blood sampling and point-of-care testing (POCT) analysis of 91 adult participants. Education was delivered in the form of a leaflet emphasizing the impact of sweetened beverage consumption on glucose regulation and the risk of insulin resistance. The results were classified into three categories: normal, pre-diabetes, and diabetes. The majority of participants (86.8%) were in the normoglycemic category. As many as 9.9% were classified as pre-diabetes and 3.3% were in the diabetes category. The average fasting blood sugar of the participants was 89.5 ± 20.1 mg/dL. These results emphasize the need for counseling regarding limiting the consumption of sweetened beverages to maintain stable blood glucose. Fasting blood sugar examination accompanied by education about sweetened beverages contributes to early detection of the risk of glucose disorders. Interventions based on examination results have the potential to increase awareness of fluid consumption patterns and encourage healthier lifestyle changes. Keywords: Fasting Blood Sugar, Sugary Drinks, Pre-Diabetes, Type II Diabetes Mellitus, Nutrition Education